Strength, behavior, and failure mode of hollow concrete masonry constructed with mortars of different strengths. (1st March 2017) - Mohamad, Gihad; Fonseca, Fernando S.; Vermeltfoort, Ad T.; Martens, Dirk R.W.; Lourenço, Paulo B.
Highlights: Block and mortar stress-strain are considered when evaluating the masonry failure. The failure mechanism of concrete masonry is a sequence of consecutive effects. The masonry failure depends on the relative strength of the mortar and block. The mortar governs the masonry failure mechanism. Abstract: This study reports the failure modes of hollow concrete masonry prisms, taking into account the block and mortar stress-strain behavior. An extensive and detailed experimental program has been conducted on three-block high stack-bonded prisms, built using a combination of one hollow block type and three mortars with different strengths. Based on the results of the experiments, masonry failure was assessed. The main conclusion of this is that the mortar in all cases governs the masonry failure mechanism. The ratio between the masonry and block moduli of elasticity, which can be used as a measure of loss of stiffness, indicates that masonry built with a strong mortar behaves almost as a homogenous material. The typical failure mode observed during testing for this type of masonry was due to tensile stresses developed in the block. A crack developed at and propagated instantly through the block face until reaching the mortar bed joint; the crack then propagated through the head joint causing a localized split at the interface between block and mortar. For masonry built with two different weak mortars, as the stress/strength ratio increased, the ratio between the masonry and mortar moduli of elasticity decreased to 0.32 and 0.55, for the weak and the weaker mortar respectively. The observed failure mode, however, was independent of how weak the mortar was since, for both cases, the masonry failed due to localized mortar crushing. Another conclusion from the study presented herein is that a robust and reliable prediction of the masonry compressive strength requires the use of the nonlinear stress-strain relationship of the component materials.